Physiological response of mung bean "Vigna radiata" plants to some bioregulators - M. A. Bekheta; I. M. Talaat (Journal of Applied Botany and Food Quality, 2012)
Pot experiments were conducted in the screen of the National Research Centre during two summer seasons 2006 and 2007 to study the physiological response of mung bean plants to some bioregulators (salicylic acid, glutathione or paclobutrazole). Vigna rediata plants were treated with different concentrations of salicylic acid (5, 10 and 15 mg/l ), glutathione or paclobutrazole (PBZ) each at 50, 100 and 150 mg/I. The obtained results indicate that foliar application of glutathione or paclobutrazole each at a rate of 150 mg/l or salicylic acid at a rate of 15 mg/l significantly increased plant height, number of branches/plant, fresh and dry weights 01' leaves, fresh and dry weights of branches and yield (g/plant). On the other hand, an application of paclobutrazole at all the used treatments led to significant decrease in the plant height. Total carbohydrates and total proteins and mineral ions content of the produced seed were significantly increased as a result of foliar application of salicylic acid, glutathione or paclobutrazole at all the used levels. All the used treatments of bioregulators caused positive changes in the gels of protein electrophoresis and photosynthetic pigments of mung bean plants.